Design and Development of the 2D Android-Based Game 'Let’s Sort It' Using the Game Development Life Cycle - Adnas, Diny Anggriani; Melisa, Melisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This research aims to design and develop a 2D Android-based educational quiz game titled “Let’s Sort It”, using the Game Development Life Cycle (GDLC) method. The purpose of the game is to help teenagers recognize and classify different types of waste, including organic, inorganic, and hazardous (B3) waste, in an engaging and interactive way. The research uses a qualitative experimental approach with a Research and Development (R&D) method, incorporating stages such as initiation, pre-production, production, testing, and release. Data were collected through questionnaires using a Likert scale distributed to teenage users after gameplay. The results show that the majority of users responded positively to the game's interface design, gameplay experience, and educational content. Users found the game enjoyable and informative, contributing to a better understanding of proper waste classification. In conclusion, “Let’s Sort It” is a feasible and effective educational tool that combines entertainment with environmental awareness, and it holds potential for further development and integration into environmental education programs.